L’informalité comme une ressource urbaine ? Le cas des favelas de Rio de Janeiro - Rafael Soares Gonçalves (EchoGéo)
This article analyzes the role played by urban informality in the process of the configuration and access to urban resources. In the case of the favelas of Rio, informality may allow access to special areas of the city, which is not possible through the market or through the application of the housing policies. It still allows the logics more functional and adapted to the needs of the residents and is indirectly and paradoxically, a resource to residents allowing them access to the city.In order to demonstrate the strategies and the impacts of the informal practices, we have chosen three cases: the practices of self-build, and then forms of informal management of water supply and, finally, the exemption from the cost of the commercial allows in the areas of the favelas.